2016
DOI: 10.1016/j.ceb.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of epithelial tissues during gap closure

Abstract: The closure of gaps is crucial to maintaining epithelium integrity during developmental and repair processes such as dorsal closure and wound healing. Depending on biochemical as well as physical properties of the microenvironment, gap closure occurs through assembly of multicellular actin-based contractile cables and/or protrusive activity of cells lining the gap. This review discusses the relative contributions of 'purse-string' and cell crawling mechanisms regulated by cell-substrate and cell-cell interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 104 publications
(123 reference statements)
5
106
0
2
Order By: Relevance
“…19 The repair process begins with the deposition of ECM proteins over the denuded epithelium. 20 The ECM matrix acts as a substrate over which the basal epithelial cells at the 'wound edge' can attach to, proliferate, flatten out and migrate over and is composed of the remnant components of the BM, such as, type IV collagen and laminin, and blood-derived factors including fibrin and fibronectin. Activation of the attenuated fibroblast sheath is evident, particularly in response to signals from the transforming growth fac- 29 This may be related to the ability of IL-13 to induce the production of TGF-b1, although IL-13 can also induce airway fibrosis in TGF-b1-independent pathways.…”
Section: Restoration Of N Ormal Airway Structure (Mod Elling)mentioning
confidence: 99%
“…19 The repair process begins with the deposition of ECM proteins over the denuded epithelium. 20 The ECM matrix acts as a substrate over which the basal epithelial cells at the 'wound edge' can attach to, proliferate, flatten out and migrate over and is composed of the remnant components of the BM, such as, type IV collagen and laminin, and blood-derived factors including fibrin and fibronectin. Activation of the attenuated fibroblast sheath is evident, particularly in response to signals from the transforming growth fac- 29 This may be related to the ability of IL-13 to induce the production of TGF-b1, although IL-13 can also induce airway fibrosis in TGF-b1-independent pathways.…”
Section: Restoration Of N Ormal Airway Structure (Mod Elling)mentioning
confidence: 99%
“…Cell adhesion molecules (fibronectin and tenascin) and cell surface receptors (integrins) appear earlier in the healing of fetal wound compared to post-native wounds, which potentially allows faster cell infiltration into the injured dermis and faster migration rate fibroblasts [25]. During fetal development, tenascin facilitates cell movement, and fibronectin facilitates anchoring.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Numerous wound healing studies in tissue culture cells and in embryos have revealed that, in many cases, lamellipodia are produced by cells at the wound margin, and these cells migrate into the wound area (reviewed in Begnaud et al, 2016). When the edges of lamellipodia meet across the gap they establish cell-cell junctions and restore the integrity of the epithelial cell sheet.…”
Section: The Oi-dic Microscope As a Tool For Live Imaging Of Wound Hementioning
confidence: 99%
“…Clytia is ideal for imaging epithelial cells because they occur as a flat squamous monolayer that covers the surface of the Clytia medusa. Epithelial cell sheets occur in all animals and are easily damaged by abrasion, surgery, or normal events such as the passage of food in the gut (Evans et al, 2013;Begnaud et al, 2016). Gaps must be rapidly closed to prevent infection and disease (Han & Ceilley, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation